Crossing Continents. Issue 3 (December 2017) - Colebrook, Claire
Abstract : This essay works through Ranjan Ghosh and J. Hillis Miller's co-authored work on thinking across continents. Taking both authors at their word I explore two senses of the continent, both of which threaten to wreak havoc on any simple or benevolent exercise of cross-cultural exchange. The first sense of continent pertains to continuity, a sense of extensive or connected land; a sense that is bound up with identity and capture. The second sense of continent hearkens back to restraint. Thinking about literature and its specific mode of inscription precludes any continuous or restrained plane of writing. What it might mean to think across continents would almost certainly require crossing our fixed sense of the continent out, and of writing incontinently.